Respuestas

2013-02-06T13:41:31+01:00

1) 2-8+3-5= (2+3)-(8+5)=5-13=-8

 

2) 2.(10-9+8-1)=2*[(10+8)-(9+1)]=2*18-10=2*8=16

 

3) ( 5-3+ 2)4=(7-3)*4=4*4=16

 

4) 1+3+8+3-1+10=(1+3+8+3+10)-(1)=25-1=24

 

5) 2+9+10-3=(2+9+10)-(3)=21-3=18

 

6) 2+8+10-3=(2+8+10)-(3)=20-3=17

2013-02-06T14:50:02+01:00

4) 1+3+8+3-1+10=(1+3+8+3+10)-(1)=25-1=24

1) 2-8+3-5= (2+3)-(8+5)=5-13=-8

 

 

2) 2.(10-9+8-1)=2*[(10+8)-(9+1)]=2*18-10=2*8=16

 

 

1) 2-8+3-5= (2+3)-(8+5)=5-13=-8

 

2) 2.(10-9+8-1)=2*[(10+8)-(9+1)]=2*18-10=2*8=16

 

3) ( 5-3+ 2)4=(7-3)*4=4*4=16

 

4) 1+3+8+3-1+10=(1+3+8+3+10)-(1)=25-1=24

 

5) 2+9+10-3=(2+9+10)-(3)=21-3=18

 

6) 2+8+10-3=(2+8+10)-(3)=20-3=17

 

3) ( 5-3+ 2)4=(7-3)*4=4*4=16

 

1) 2-8+3-5= (2+3)-(8+5)=5-13=-8

 

5) 2+9+10-3=(2+9+10)-(3)=21-3=18